Delimitation in the Veratrum mengtzeanum—V. chiengdaoense complex (Melanthiaceae) in Thailand based on morphology, with commentary on conservation status - Trias-Blasi, Anna; Suksathan, Piyakaset (Phytotaxa, 2013)
The two species of Veratrum in Thailand, V. mengtzeanum and V. chiengdaoense, are supported as conspecific with a detailed morphological study. Two distinct subspecies of V. mengzeanum s.l. are defined based on morphology and distribution, and a new subspecies, Veratrum mengzeanum subsp. phuwae is described. Conservation assessments are provided for both subspecies.